May Diet and Dietary Supplements Improve the Wellness of Multiple Sclerosis Patients? A Molecular Approach. (30th December 2010) - Riccio, Paolo; Rossano, Rocco; Liuzzi, Grazia Maria
Abstract : Multiple sclerosis is a complex and multifactorial neurological disease, and nutrition is one of the environmental factors possibly involved in its pathogenesis. At present, the role of nutrition is unclear, and MS therapy is not associated to a particular diet. MS clinical trials based on specific diets or dietary supplements are very few and in some cases controversial. To understand how diet can influence the course of MS and improve the wellness of MS patients, it is necessary to identify the dietary molecules, their targets and the molecular mechanisms involved in the control of the disease. The aim of this paper is to provide a molecular basis for the nutritional intervention in MS by evaluating at molecular level the effect of dietary molecules on the inflammatory and autoimmune processes involved in the disease.